Effects of Increasing Space Allowance by Removing a Pig or Gate Adjustment on Finishing Pig Growth Performance - C. Holder; C. Carpenter; M. D. Tokach; J. M. DeRouchey; J. C. Woodworth; R. D. Goodband; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 256 pigs (PIC 327 × 1050; initially 123.1 lb) were used in a 71 d growth study to compare the effects of increasing space allowance by removing a pig or gate adjustment, on finishing pig growth performance. At the initiation of the trial, pens of pigs were blocked by BW and allotted to 1 of 4 space allowance treatments. The 4 treatments included: 1) 9.8 ft2/pig or 2) 6.8 ft2/pig for the entire study with treatments 3 and 4 initially providing 6.8 ft2, but either a gate was adjusted or the heaviest pig in the pen was removed to provide more space. By using the following equation, space adjustments were made to keep the pigs above their predicted minimum space requirement before growth is impacted: space [(m2) = 0.0336 × BW (kg)0.66]. There were initially 8 pigs per pen and 8 pens per treatment. From d 0 to 28, before any gate adjustments or pig removals, ADG tended to be greater (P = 0.076) for pigs allowed 9.8 ft2compared with pigs stocked at 6.8 ft2. Overall, d 0 to 71, pigs allowed 9.8 ft2had greater (P = 0.001) ADG compared with pigs with all other space allowances. Removing pigs or adjusting the gating increased (P = 0.001) ADG compared to those maintained at 6.8 ft2; however, both treatments had decreased (P = 0.001) ADG compared with pigs allowed 9.8 ft2. Most of the differences in ADG can be explained by differences in ADFI. Pigs allowed 9.8 ft2had greater (P = 0.001) ADFI compared with pigs allowed 6.8 ft2; however, intake was similar for pigs allowed increased space by gate adjustment to pigs allowed 9.8 ft2. Pigs allowed increased space by pig removal had similar ADFI to pigs allowed 6.8 ft2. Space allowance did not influence feed efficiency. In summary, as expected, pigs with 9.8 ft2grew faster and consumed more feed than pigs that were restricted in space. Furthermore, either removing a pig or adjusting the gating as pigs reached the critical k value influenced growth performance similarly. We speculated that along with pig growth, removing the heaviest pigs could have influenced social dynamics of the remaining pigs in the pen; however, our study indicates the performance benefit from removing the heaviest pig from the pen is primarily from the increased space allowance alone. As pigs grew to the minimum predicted space requirement and were subsequently allowed more space, performance was not similar compared to unrestricted pigs. This indicates the industry accepted minimum space prediction equation [m2= 0.0336 × BW (kg)0.66] doesn’t fully explain the impacts on pig performance across multiple body weight ranges.
Keywords: space allowance; K-value; marketing